Sexual behaviour and stridulation during mating in Triatoma infestans (Hemiptera: Reduviidae). - Manrique, G. (1994)
Factors affecting mating behaviour in the bug Triatoma infestans were quantitatively studied in the laboratory. Experimental conditions were established so that the probability of copulation increased with the time elapsed since the first adult meal. Copulatory attempts by males did not vary as a function of time, but rejections by females became significantly less frequent with the post feeding time. Non-receptive females displayed four types of rejection behaviour, i.e. flattening, stridulation, evasion and abdominal movements. The occurrence of stridulation performed by females in a sexual context was observed in a regular fashion and was quantified for the first time in this species.